DEMOKRASI POLITIK SAMPAI WARISAN RADIKALISME; SEBUAH PENGETAHUAN NASIONALISME ERA MILENIAL - Fajar, Fajar (JPP (Jurnal Politik Profetik), 2018)
State and its function are conducted by institution mediated by contesting political parties within democratic events called ‘public election.’ This contestation works as public space where power is identified as electoral ceremony regulated through laws of election. Power is assigned by public power to the lawmaker or legislative power. This style of government has then been in line with regulated laws, not to accommodate the rich, nor to the poor, but applies for the sake of the whole. In an independent situation, political equality is critical. A medieval formula of independence states that salus populi supremelex (people welfare is the grandiose law). In preserving such principal rights, unfair treatment between the rich and the poor frequently occurs, which within some circumstance, leads to radical movement by certain group of insurgents. This typical group resists against the ruling government and complaining about the former’s lack of access towards their principal rights of property, by which they believe that all conditions to guarantee the welfare of the people should be proportionally and equally available.